Thalictrum foliolosum: A lesser unexplored medicinal herb from the Himalayan region as a source of valuable benzyl isoquinoline alkaloids. (12th June 2020) - Sharma, Nitin; Kumar, Vikas; Chopra, Mahendra Pratap; Sourirajan, Anuradha; Dev, Kamal; El-Shazly, Mohamed
Abstract: Ethnopharmacological relevance: Thalictrum foliolosum DC (Ranunculaceae) is a perennial flowering herb traditionally used as a tonic, antiperiodic, diuretic, febrifuge, purgative and stomachic and for the treatment of snakebite, jaundice, and rheumatism. Aim of the study: To provide a critical assessment of the state-of-the-art related to the traditional uses, phytochemistry, and pharmacology of T. foliolosum with the ultimate objective of providing further research strategies to facilitate the exploitation of the therapeutic potential of T. foliolosum for the treatment of human disorders. Materials and methods: Exhaustive bibliographic research related to T. foliolosum plant was carried out using scientific research engines and databases such as Google Scholar, PubMed, Web of Science covering all retrieved relevant manuscripts written in English. Results: Several alkaloids such as berberine, jatrorrhizine, palmatine, thalrugosidine, thalrugosaminine, thalisopine (thaligosine), thalirugidine, thalirugine, 8-oxyberberine (berlambine), noroxyhydrastinine, N, O, O-trimethylsparsiflorine, thalicarpine, thalidasine, thalfoliolosumines A and thalfoliolosumines B were reported from T. foliolosum . Ethnomedicinal studies revealed much wider scope of T. foliolosum in developing various drugs to solve multiple challenges in the health sector. Therapeutic effects were attributed to the bioactivities of the secondary metabolites present in T. foliolosum . Conclusions: T. foliolosum is rich in berberine and other benzylisoquinoline alkaloids. T. foliolosum can be used as an excellent and effective herbal remedy for various human ailments since there are no reports on the toxicity of this herb. Graphical abstract: Image 1